Pengaruh Pemahaman Al-Qur’an dan Hadis tentang Toleransi terhadap Sikap Sosial Siswa MAN 1 Pekalongan: Studi Observasi dalam Interaksi Antar Siswa - Alya Faradilla (Al-Nizam: Indonesian Journal of Research and Community Service, 2024)
Abstract: The purpose of this study was to determine how students' understanding of the teachings of the Qur'an and Hadith impacts their social tolerance at MAN 1 Pekalongan. Tolerance is an important value that must be instilled in this increasingly complex era of globalization, especially among the younger generation. This study investigates how contextual and textual understanding of the Qur'an and Hadith can shape inclusive social attitudes and respect differences. The results of the study indicate that a strong understanding of the principles of tolerance found in the Qur'an and Hadith, such as religious freedom, fairness, and brotherhood, helps create a better learning environment. But tolerance is still difficult to implement, and schools must continue to teach. This study makes an important contribution to character development and religious moderation in schools, helping students become open people and respect diversity in society. Keywords: Al-Quran; Hadith; Tolerance; Social Attitude; Students.